Analysis of Entrepreneurship Activities in Rice Farming - Mumuh Mulyana; Harianto Harianto; Dedi Budiman Hakim; Sri Hartoyo; Mariyah Mariyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The demand for rice as a basic need of the Indonesian people in meeting food needs encourages farming to have good farming performance and be able to provide optimal results. Achievements performance farming will determine by the farmer and other factors that influence it good internal factors and external. Farmer as manufacturers in the field agriculture often Act as price takers. Ability farmer in allocate factor production and other factors with alternatives combination new could produce performance different farming. This other factor is entrepreneurship (entrepreneurship). Entrepreneurship in the agricultural sector can create and provide value-added products or new innovations, making people more creative, independent and able to develop agricultural businesses into business. Study this aim to analyze the Entrepreneurial Activities of Rice Farmers in the District Bojong Picung Regency Cianjur. Primary data collection time starts June-December 2019. Data used is hard data latitude (cross section) of 167 farmers paddy rice. Analysis activity entrepreneurship use Entrepreneurial Behavioral Index (EBI) with enter component measurement Entrepreneurship in farming proposed by the Food and Agriculture Organization (FAO) consists of: on 4 (four) indicators, namely: Entrepreneurial Qualities, Entrepreneurial Competencies, Managerial Competencies, Technical Competencies. Research results show that activity entrepreneurship in the District Bojongpicung Cianjur included in the medium category with an EBI value of 56.15. Farmer with high EBI category by 22.75 percent, in the medium EBI category at 50.90 percent, and in the low EBI category by 26.95 percent. This EBI Assessment seen from motivation farmers who make farming as profession main, ability farmer in build network with involved in group farm and courage take risk with no follow insurance agriculture, skills managerial specifically in ownership status land and setting plant, and input and production management farming carried out. Implication study this is activity entrepreneurship could Upgrade performance farming. Ability entrepreneurship could push farmer apply more management good in management farming and quality individual farmers who have motivation, courage take risk, and build good cooperation network so that farmer could own power competitive.